Environment-assisted crack nucleation in La(Fe, Mn, Si)13-based magnetocaloric materials. (March 2022) - Wang, Siyang; Lovell, Edmund; Guo, Liya; Wilson, Neil; Ryan, Mary P.; Giuliani, Finn
Highlights: Freshly focussed-ion-beam-polished surfaces exposed to air. La-rich phase (La2 O3 ) expands in air due to hydroxylation reaction. Cracks in La(Fe, Mn, Si)13 appear near these expansions. Formation/size of La2 O3 should be suppressed to avoid local cracking. Abstract: Cracking in La(Fe, Si)13 -based magnetocaloric materials has been observed to predominantly form around La-rich (La2 O3 ) particles and pose a threat to their long-term structural integrity. To understand the formation of these cracks, FIB cross-sectional polishing followed by SEM characterisation was employed to study local microstructural evolution after air exposure. Results suggest that volume expansion and internal degradation associated with a chemical reaction between La2 O3 particles and water/moisture can lead to crack nucleation in the 1:13 phase adjacent to La-rich particles. This observation indicates that the formation of La-rich particles should be suppressed, or their size minimised during material processing to ensure the long-term structural integrity of La(Fe, Mn, Si)13 magnetocaloric materials.